An actor's handbook - Stanislavski, Constantin (London Methuen, 1924)
"I have felt there was nothing for me to do except to devote my labour and energy almost exclusively to the study of Creative Nature...I have acquired a sum of experience in the course of long years of work and this is what I have sought to share with you." (Stanislavski)Here in concise form is what Stanislavski said about acting, alphabetically arranged to aid students, professionals and lay people interested in the stage craft. These collected short statements on a variety of subjects cannot replace the full expression of Stanislavski's ideas and discoveries in his other books, but they will serve to refresh the reader's memory and pinpoint what Stanislavski has to offer enquiring minds both in and out of the theatre.